Modern approach to determining the heterogeneity of cast iron - Глушкова, Д. Б.; Волчук, В. М.; Hlushkova, Diana; Volchuk, Volodymyr (Харківський національний автомобільно-дорожній університет, 2025)
In the process of designing and optimizing materials for industrial applications, there is a need for a comprehensive analysis of their mechanical properties. Some of these properties, by their physical nature, have opposite growth trends. In particular, an increase in the hardness of ironcarbon alloys is accompanied by a decrease in plasticity and an increase in brittleness, which makes it difficult to achieve an optimal balance between these characteristics. In this regard, the task of assessing the area that defines the limits of the combination of mechanical properties, or the so-called compromise area, arises. For the study, short-rolling rolls produced by the USSR Steel Mill were selected, and the sample was based on 283 melts with a total mass of over 800 tons. Analysis of cast iron rolls manufactured using the SSCHN technology allowed us to determine the compromise area, which includes the ranges of permissible values of mechanical properties: tensile strength (σВ) within 240–460 MPa, bending strength (σЗГИН) in the range of 330–940 MPa, impact strength (KS) from 9 to 33 kJ/m² and Shore hardness (HSD) within 40–60 units. These values were obtained taking into account the full range of material cooling parameters in metal molds. The proposed method for assessing the compromise area makes it possible to set priorities regarding the set of mechanical characteristics of rolls required by the consumer, to predict changes in the parameters of the technological process and to carry out its adaptive adjustment. In particular, the methodology provides for the possibility of automated regulation of the chemical composition of the material in accordance with the specified operating conditions.
Сучасний підхід до визначення неоднорідності чавуну
Keywords: carbon alloys; multiracial; structure; hardness; statistical dimensions; orderliness; regularity; вуглецеві сплави; мультифрак- тал; структура; твердість; статистичні роз- мірності; впорядкованість; регулярність; 519.21; 10.30977/BUL.2219-5548.2025.108.0.33